A Representative National Police Commission in Realizing the Professionalism of the Indonesian National Police - Sri Widayatai; Diana Haiti; Rahmida Erliyani; Anang Shophan Tornado (Journal of Law, Politic and Humanities, 2026)
The National Police of the Republic of Indonesia (Polri) has a vital constitutional mandate, but the integration of large authorities without strong external oversight creates a risk of abuse of authority and a decline in public trust. This study aims to analyze the nature of the position and juridical limitations of the National Police Commission (Kompolnas) and formulate the urgency of reconstructing the institution so that it becomes representative in realizing the professionalism of the National Police. Using normative legal research methods with a qualitative approach, this study dissects the position of the National Police Commission as a state auxiliary organ through the theory of representative bureaucracy. The findings of the study show that the National Police Commission experiences normative ambiguity and an "authority gap" because its legal basis is only based on Presidential Regulations, so it does not have investigative and executive authority. In addition, the dominance of government elements ex-officio injures independence and creates a conflict of political interests. As a solution, this study concludes the need to transform the legal basis of the National Police Commission into an independent law that provides immunity rights, investigative authority, and integrates the values of local wisdom such as Siri' Na Pacce and Piil Pesenggiri as moral instruments. This reconstruction is crucial to ensure that the National Police is transformed into a humane, accountable, and trusted institution in the democratic era.